2004
DOI: 10.1017/s0266462304001175
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the publication of health research

Abstract: Objectives: Assess the degree to which research project findings were published and explore factors that influenced publication. Methods: Questionnaire to project leaders. Classification of publications and findings. Chi-squared; univariate and multivariate Cox regression analyses. Results: Forty percent of projects published in peer-reviewed journal; highly statistically significant relationships between publication in peer-reviewed journals and (1) projects in Responsive/Fellowships streams (p = .045); and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…Fifteen empirical studies were deemed eligible [3]–[5], [13][15], [17], [18], [21], [26][29], [31], [32].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifteen empirical studies were deemed eligible [3]–[5], [13][15], [17], [18], [21], [26][29], [31], [32].…”
Section: Resultsmentioning
confidence: 99%
“…SCOPUS identified eight of the included empirical studies [3]–[5], [13][15], [26], [29]. The search of the Cochrane Methodology Register identified 15 included empirical studies [3]–[5], [13][15], [17], [18], [21], [26][29], [31], [32]. Seven studies were identified by all three databases [4], [5], [13], [14], [15], [26], [29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] Studies have identified that undergraduate medical research helps the students to understand medicine and improve clinical skills, [5] apply what they study in a practical way, [6] improve confidence and problem-solving skills, [7] and communication skills. [8,9] A research activity requires to adopt the steps and procedure in a rational routine. There is to be a perfect link between the steps, initiated with the purpose of the study, resulting through literature review, theoretical framework, research question, methodology section, data analysis, and the findings.…”
Section: Introductionmentioning
confidence: 99%